The status of knowledge, attitudes, and practice in the cultivation and usage of improved forages in Kenya and Uganda - Sibiko, Kenneth W.; Lukuyu, Margaret N.; Notenbaert, An Maria Omer; Burkart, Stefan (International Center for Tropical Agriculture, 2023)
There is a scarcity of published literature about farmers’ level of knowledge, attitudes, and practices regarding improved forage varieties in East Africa, particularly among the populations where development projects have been and continue to be implemented. This study was carried out to address this knowledge gap and strengthen future scaling activities. We rely on cross-sectional data with a sample of 353 respondents equally drawn from treatment and control areas across 3 districts in Kenya and Uganda respectively. Pairwise correlations, t-tests, and left-censored Tobit regression were utilized for the analysis. Results indicate that treatment areas have significantly higher levels of knowledge and have more positive attitudes toward improved forage cultivation and use compared to the control areas. However, Kenyan farmers seemed generally more knowledgeable (at 3.16 on a scale of 1-5) and portrayed positive attitudes than their Ugandan counterparts (2.18) within the intervention areas. Regarding the actual forage adoption, it is observed that the majority (91%) of the respondents in Kenya cultivated at least one forage crop on their farms, which was more than double the percentage (38%) who cultivated forages in Uganda. The most important factors influencing the area planted with forages were participation in forage training events, the size of land and number of cattle owned, as well as the education and experience levels of farmers. In Kenya, we also observed a significant positive correlation between different extension approaches (radio programs, attending field days, TV programs, farmer field schools, farmer-to-farmer exchange, formal workshops) and the respondents’ knowledge levels. The findings show that a great milestone has been achieved in creating awareness among Kenyan farmers. Similar intensified campaigns will be required in Uganda and other East African countries to scale out the adoption of high-quality forages in these countries.